Recollection of past memories in Croatia - Ilir Kalemaj (Politikon, 2008)
The end of Communist era and the end of Marxist-Leninist ideology that occupied the Central and Eastern European space for half a century, proved a blessing in many regards for these countries, enabling them to push forward with democratic and free-market reforms that in long run would culminate in their eventual democratization, prosperity and joining European Union. A rather awkward exception to this rule has been the former federation of Yugoslavia, which experienced an abrupt change fromTito`s somewhat relaxed communism toward a violent disintegration that cost thousands of lives, exhausted billions of dollars and left behind wreckage and devastation, whose imprints can be still distinguished. It is rather puzzling that Yugoslavia did not experience any kind of (liberal)-democratic opposition, or that long time dissidents of the communist regimes like Milovan Djilas, Dobrisa Cosiü or Franjo Tudjman to mention just a few, instead of being promoters of an organized opposition to the regime, were either marginalized or turned nationalists, leaving thus little room for a peaceful, democratic change that was the norm elsewhere. A lot of explanations are offered of why this violent disintegration took place anddifferent. Interpretations of the empirical observations, ranging from elite conspiracies to electorate pressure to foreign intervention as the main causes of the breakdown of the state and eventually war. Nevertheless, it seems that efforts of state-building through a reshaping of the understanding of nationalist identities and the means employed for such ends have been rather missed from the existing literature, especially in the case of Croatia.